1999
DOI: 10.1096/fasebj.13.14.1961
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the insulin receptor in caveolae of adipocyte plasma membrane

Abstract: The insulin receptor is a transmembrane protein of the plasma membrane, where it recognizes extracellular insulin and transmits signals into the cellular signaling network. We report that insulin receptors are localized and signal in caveolae microdomains of adipocyte plasma membrane. Immunogold electron microscopy and immunofluorescence microscopy show that insulin receptors are restricted to caveolae and are colocalized with caveolin over the plasma membrane. Insulin receptor was enriched in a caveolae-enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
317
3
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(350 citation statements)
references
References 64 publications
(69 reference statements)
27
317
3
3
Order By: Relevance
“…Although there is missing information on Mest and Sfrp5 gene expressions and their regulation in the process of ageing, caveolae are currently being intensively studied. Recent research has shown that adipocytes from animals in a process of ageing presented a decrease in mean expression of caveolar proteins per unit cell surface (Hulstrom et al 2013); in addition, Cav1 was reported to be relevant for insulin signaling in AT (Gustavsson et al 1999).…”
Section: Adipose Tissue Expansionmentioning
confidence: 99%
“…Although there is missing information on Mest and Sfrp5 gene expressions and their regulation in the process of ageing, caveolae are currently being intensively studied. Recent research has shown that adipocytes from animals in a process of ageing presented a decrease in mean expression of caveolar proteins per unit cell surface (Hulstrom et al 2013); in addition, Cav1 was reported to be relevant for insulin signaling in AT (Gustavsson et al 1999).…”
Section: Adipose Tissue Expansionmentioning
confidence: 99%
“…For inhibition of clathrin-dependent endocytosis, samples were pretreated with 8 g/ml chlorpromazine (CPZ; Gustavsson et al, 1999;Okamoto et al, 2000) or were potassium depleted (Larkin et al, 1983;Hansen et al, 1993); for disruption of caveolar endocytosis, cells were pretreated with 25 g/ml nystatin (Rothberg et al, 1992) or 200 M genistein (Aoki et al, 1999;Chen and Norkin, 1999;Liu and Anderson, 1999 g/ml DNA using the manufacturer's protocol. After a 4 -6-h treatment, the cells were washed and subsequently cultured for 24 -48 h in DMEM containing 10% FBS before treatment with the fluorescent lipids or toxins as above.…”
Section: Pharmacological Inhibitors Of Endocytosismentioning
confidence: 99%
“…These specific membrane compartments, also commonly referred to as the lipid rafts, are composed of cholesterol and glycolipids [1,2], and predominantly harbor a host of receptors and signaling molecules, allowing them to mediate a variety of cellular events, including cellular signaling, pathogenic invasion, immune responses, and cholesterol homeostasis [3][4][5][6]. Because the lipid rafts are loaded with many receptors for epidermal growth factor (EGF) [7], platelet-derived growth factor [8], nerve growth factor [9], insulin [10], insulin-like growth factor [11], transforming growth factor [12], and tumor necrosis factor [13], these rafts might act as platforms which initiate various cellular signal pathways.…”
Section: Introductionmentioning
confidence: 99%